Informed Consent in Clinical Practice and Research and Its Awareness among Under Graduate Medical Students - S.R. Saritha1, C.S. Sreedevi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Consent denotes voluntary agreement, permission or compliance. Informed consent in medical practice is the grant of permission by a patient for an act to be carried out by a doctor, such as a diagnostic, surgical or therapeutic procedure. Informed Consent in research is the voluntary agreement to participate in the study.The study was undertaken with the objective to assess the level of knowledge regarding informed consent among Second MBBS undergraduate medical students at the beginning of the class by a pretest and to demonstrate measurable gain in knowledge at the end of the class by a posttest using the same questionnaire.This quasi-experimental study conducted in the Department of Forensic Medicine, Govt.T.D Medical College, Alappuzha, among 118 students using a structured and close ended, pretested questionnaire containing 13 multiple choice questions.Statistical analysis done on average pre and posttest score and on difference in pre and posttest responses to individual questions; revealed measurable gain in knowledge at the end of the class, since p value was < 0.05.